CRITERIA AND INDICATORS OF FORMATION OF HUMANISTIC AND VALUE ATTITUDE OF PRIMARY SCHOOLCHILDREN TOWARDS THEMSELVES - Holiuk, Oksana; Pakhalchuk, Natalia; Rodiuk, Nataliia; Demchenko, Olena; Kit, Galina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Scientific works show that it is necessary to solve the humans problem of the formation of values and value attitude. Early school age is a period of active development of ideological orientations, interests, behavioral strategies, assessments and self-evaluation. The purpose of the study lay in developing and testing the diagnostic tools of the formation of a humanistic and value attitude of the schoolchildren towards themselves and in determining on this basis the appropriate pedagogical conditions for improving the investigated quality. The primary schoolchildren (n = 317, age 8-9) took part in the study. The results of the preliminary stage of the pedagogical experiment revealed the need to raise the level of humanistic and value attitude of children (low level – 61,5%, average level – 30,9%, high level – 7,6%). Primary school teachers are important organizers of the educational process with students, but they do not use enough methods that are effective in solving this research problem. In order to humanize the environment in primary school, authors suggest using game exercises, conversations, elements of training, including children in various types of socially significant activities, creating axiological educational situations, etc.